An In Vitro and In Vivo Comparison of Cartilage Growth in Chondrocyte-Laden Matrix Metalloproteinase-Sensitive Poly(Ethylene Glycol) Hydrogels with Localized Transforming Growth Factor β3 - Schneider, Margaret C. (Acta Biomater, 2019)
While matrix-assisted autologous chondrocyte implantation has emerged as a promising therapy to treat focal chondral defects, matrices that support regeneration of hyaline cartilage remain challenging. The goal of this work was to investigate the potential of a matrix metalloproteinase (MMP)-sensitive poly(ethylene glycol) hydrogel containing the tethered growth factor, TGF-β3, and compare cartilage regeneration in vitro and in vivo. The in vitro environment comprised chemically-defined medium while the in vivo environment utilized the subcutaneous implant model in athymic mice. Porcine chondrocytes were isolated and expanded in 2D culture for 10 days prior to encapsulation. The presence of tethered TGF-β3 reduced cell spreading. Chondrocyte-laden hydrogels were analyzed for total sulfated glycosaminoglycan and collagen contents, MMP activity, and spatial deposition of aggrecan, decorin, biglycan, and collagens type II and I. The total amount of extracellular matrix (ECM) deposited in the hydrogel constructs was similar in vitro and in vivo. However, the in vitro environment was not able to support long-term culture up to 64 days of the engineered cartilage leading to the eventual breakdown of aggrecan. The in vivo environment, on the other hand, led to more elaborate ECM, which correlated with higher MMP activity, and an overall higher quality of engineered tissue that was rich in aggrecan, decorin, biglycan and collagen type II with minimal collagen type I. Overall, the MMP-sensitive PEG hydrogel containing tethered TGF-β3 is a promising matrix for hyaline cartilage regeneration in vivo.